Duck Interleukin-22: Identification and Expression Analysis in Riemerella anatipestifer Infection. (11th November 2021) - Flores, Rochelle A.; Cammayo, Paula Leona T.; Nguyen, Binh T.; Fernandez-Colorado, Cherry P.; Kim, Suk; Kim, Woo H.; Min, Wongi
Abstract : Riemerella anatipestifer is one of the most devastating pathogens affecting the global duck farms. Infection is involved in secretion of proinflammatory cytokines, including interleukin- (IL-) 17A. During the immune response to infection, IL-22 and IL-17A are often produced concurrently and at high levels in inflamed tissues. Little is known about duck IL-22 (duIL-22) during R. anatipestifer infection. We describe the characterization of duIL-22 and its mRNA expression analysis in splenic lymphocytes and macrophages treated with heat-killed R. anatipestifer and in the spleens and livers of R. anatipestifer -infected ducks. Full-length cDNA of duIL-22 encoded 197 amino acids. The deduced amino acid sequence of duIL-22 shared a 30.4–40.5% similarity with piscine counterparts, 57.4–60.1% with mammalian homologs, and 93.4% similarity to the chicken. Duck IL-22 mRNA expression level was relatively high in the skin of normal ducks. It was increased in mitogen-stimulated splenic lymphocytes and in killed R. anatipestifer -activated splenic lymphocytes and macrophages. Compared with healthy ducks, IL-22 transcript expression was significantly upregulated in the livers and spleens on days 1 and 4 postinfection, but not on day 7. IL-17A was significantly increased in the spleens only on day 4 postinfection and in the livers at all time points. When splenic lymphocytes were stimulated with heat-killed R. anatipestifer, CD4 + cells predominantly produced IL-22 while IL-17A was expressed both by CD4 + and CD4 - cells. These results suggested that IL-22 and IL-17A are likely expressed in different cell types during R. anatipestifer infection.